Pengendalian Persediaan Bahan Baku Jamu Madura Menggunakan Metode Economic Order Quantity (EOQ) - Asfa, Dian Farida; Maflahah, Iffan; Ghooniyah , Indriana Mahrotul (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
The raw material control process is a very important activity that must be considered by every industry in order to meet consumer needs. The purpose of this study is to control the inventory of raw materials at PT Firdaus Kurnia Indah which produces Madura herbal medicine because of the seasonal nature of the spice raw materials and the shortage of raw materials for production. The method used is the EOQ (Economic Order Quantity) method. The results of data analysis using the EOQ method obtained an economical order quantity for raw materials for Madura herbal medicine at PT Firdaus Kurnia Indah, namely 312 kg of manjakani, 200 kg of kunci pepet, 184 kg of young pinang, 68 kg of turmeric, 130 kg of pomegranate and 226 kg of kayu rapet, with an order frequency of once a year. The total inventory cost using the EOQ method is Rp 159,756, this saves inventory costs by 87,55% compared to the existing method of PT Firdaus Kurnia Indah. Thus, it can be concluded that the application of the ABC and EOQ methods is the best solution for the company PT Firdaus Kurnia Indah.